Changing equation to x equals

Im currently stuck on this equation I need to modify to be in terms of x

$$y=-x^2+4$$

I got something like this which looks wrong

$$x = -\sqrt{y+4}$$

First you would subtract the 4 from both sides. Do you then divide by -1 then square root it?

• Solve according to SAMDEB. Solving an equation is the unraveling of an evaluation, so you need to reverse the steps that you would normally use to evaluate an expression. If I gave you instructions on how to get to Wal-Mart, could you find your way back home again? It's the same idea. – John Joy Aug 29 '15 at 4:05

You should divide by $-1$ and then square root it. In the original equation, it is $y = -(x^2) + 4$. Doing this should get you $x = \sqrt{4-y}$.
• Don't forget the $\pm$ – abiessu Aug 29 '15 at 3:36
• should it be $$\pm \sqrt{4-y}$$ ? – MD_90 Aug 29 '15 at 3:38
• @MD_90, yeah it should have a $\pm$ as abiessu pointed out. I've always thought that the $\pm$ is implied by the radical sign. – Mike Pierce Aug 29 '15 at 3:39
Original equation, $y=-(x^2)+4$; Minus $4$ from both sides, $y-4=-x^2;$ Multiply $(-1)$ to both sides, $x^2=-(y-4)$; That gives you, $x^2=4-y$; Square root it, $x=\pm\sqrt {4-y}$ Final ans is $x=\pm\sqrt {4-y}$.